Research on the Current Situation and Countermeasures of Ecological Environment Management of Laos: Tourism Industry-taking Luang Prabang City as a Case Study - chanmany, phouthasack; xǐ, Zhūsì; dàxué, Gāo (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The research aims to assess these environmental challenges and identify effective countermeasures by examining governance structures, community involvement, and stakeholder perspectives. Using a mixed-methods approach, the study combines qualitative data from document analysis, field observations, and 30 semi-structured interviews with government officials, community leaders, business owners, and NGOs, alongside quantitative survey data from 200 residents and tourists. Findings reveal a significant decline in ecological assets, particularly the disappearance and pollution of urban ponds, attributed to unregulated land-use changes and insufficient environmental oversight. Institutional weaknesses, including fragmented governance, lack of enforcement, and limited funding, further exacerbate these problems. Despite these challenges, the study identifies several promising countermeasures. Community-led Pond management projects, eco-certification of tourism enterprises, and decentralized waste treatment initiatives show potential for scaling up. Both residents and tourists express strong support for more sustainable tourism practices, though implementation remains limited without integrated policy support. The research concludes that effective environmental management in Luang Prabang requires a more coherent and collaborative strategy, grounded in participatory governance, updated regulatory frameworks, and sustainable financing mechanisms. Protecting Luang Prabang’s ecological integrity is essential not only for the health of its local communities and ecosystems but also for preserving the long-term viability of its tourism industry. This study contributes to the broader discourse on sustainable tourism in Southeast Asia and provides practical recommendations for improving environmental governance in culturally and ecologically sensitive destinations.